Health information orientation and health literacy as determinants of health promotion behaviors in adolescents: a cross-sectional study - You, Mi-Ae; Ahn, Jeong-Ah (Frontiers in Public Health, 2025)
IntroductionThis cross-sectional study aimed to identify the impact of health information orientation and health literacy on adolescents’ health-promoting behaviors.MethodsWe enrolled 149 middle school students from an urban city in South Korea through convenience sampling. The data was collected in October 2022 using a self-reported questionnaire. Health information orientation was measured using the Health Information Orientation Instrument (Cronbach’s α = 0.86). Health literacy was assessed with the Korean Adolescent Health Literacy Scale (KR-20 = 0.66), and health promotion behaviors were evaluated using the Adolescent Health Promotion Scale-Short Form (Cronbach’s α = 0.89). Analysis methods included independent t-tests, one-way ANOVA, and multiple regression.ResultsResults indicated significant differences in health promotion behaviors based on perceived health status, economic status, primary health-related information provider, and health literacy. Health information orientation showed a strong positive correlation with health promotion behaviors. The factors that influenced health promotion behaviors were health information orientation, primary information provider, economic status, and health literacy.DiscussionFindings suggest that school and community health promotion programs should engage adolescents and parents to enhance health literacy and proactive information-seeking behaviors for improving the health outcomes of adolescents.